Puccinia striiformis f. sp. tritici effectors in wheat immune responses - Wu, Nan; Ozketen, Ahmet Caglar; Cheng, Yu; Jiang, Wanqing; Zhou, Xuan; Zhao, Xinran; Guan, Yaorong; Xiang, Zhaoxia; Akkaya, Mahinur S. (Frontiers in Plant Science, 2022)
The obligate biotrophic fungus Puccinia striiformis f.sp. tritici, which causes yellow (stripe) rust disease, is among the leading biological agents resulting in tremendous yield losses on global wheat productions per annum. The combatting strategies include, but are not limited to, fungicide applications and developing resistant cultivars. However, the evolutionary pressure drives rapid changes, especially in its "effectorome" repertoire, thus allowing pathogens to evade and breach the resistance. The extra- and intra-cellular effectors, predominantly secreted proteins, are tactical arsenals aiming for many defense processes of plants. Hence, the identity of the effectors and the molecular mechanisms of the interactions between the effectors and the plant immune system have long been targeted in research. The obligate biotrophic nature of the Puccinia striiformis f.sp. tritici and the challenging nature of its host, the wheat impedes research on this topic. Next-generation sequencing and novel prediction algorithms in bioinformatics, which are accompanied by in vitro and in vivo validation approaches offer a speedy pace for the discovery of new effectors and investigations of their biological functions. Here, we briefly review recent findings exploring the roles of Puccinia striiformis f.sp. tritici effectors together with their cellular / sub-cellular localizations, host responses, and interactors. The current status and the challenges will be discussed. We hope the overall work will provide a broader view of where we stand, and a reference point to compare and evaluate new findings.